Role of incident kinetic energy of adatoms in thin film growth - Müller, Karl-Heinz (Surface science letters, 1987)
Film growth as a function of incident kinetic energy of adatoms is studied by employing two-dimensional molecular dynamics simulations for Lennard-Jones particles. At thermal incident kinetic energies films exhibit a high void and defect content when grown on a zero temperature substrate. Films grown at adatom incident kinetic energies typical for sputter deposition show higher average density and improved epitaxy due to the larger impact mobility of condensing atoms.